2021
DOI: 10.1089/jmf.2020.0034
|View full text |Cite
|
Sign up to set email alerts
|

Mildly Processed Natural Eggshell Membrane Alleviates Joint Pain Associated with Osteoarthritis of the Knee: A Randomized Double-Blind Placebo-Controlled Study

Abstract: Poor joint health is a significant burden to society. Millions of people suffer from some form of joint-related disorder or disease, most often osteoarthritis (OA). It was hypothesized that chicken eggshell membrane (EM) is effective in the regeneration of cartilage and/or immunomodulation (oral tolerance), and as such relieves pain and stiffness in joints commonly affected in arthritis. We tested this hypothesis in a double-blind, placebo-controlled EM intervention study. Of 150 male and female volunteers, 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…Although all of the groups registered a decrease in perceived pain, both doses used in this study induced a bigger reduction than in the control group, indicating a relationship between eggshell membrane consumption and reduction in pain. Such results are compatible with previous studies that demonstrated the efficacy of this nutraceutical to alleviate knee pain, symptomatology, and joint functionality [ 14 , 15 , 16 , 17 , 18 , 19 ]. These results are higher than those registered for other supplements such as curcuma [ 12 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Although all of the groups registered a decrease in perceived pain, both doses used in this study induced a bigger reduction than in the control group, indicating a relationship between eggshell membrane consumption and reduction in pain. Such results are compatible with previous studies that demonstrated the efficacy of this nutraceutical to alleviate knee pain, symptomatology, and joint functionality [ 14 , 15 , 16 , 17 , 18 , 19 ]. These results are higher than those registered for other supplements such as curcuma [ 12 ].…”
Section: Discussionsupporting
confidence: 93%
“…Although previous studies addressed the study of the efficacy of eggshell membrane as a supplement to alleviate knee joint pain [ 14 , 15 , 16 , 17 , 18 ], here, for the first time, two quantitative variables (mobility and strength of knee joint), as well as qualitative ones (pain, functional ability, and sleep quality), were monitored to accurately evaluate changes in the quality of life of subjects affected by this common pathology. Such a variable set extends the findings of previous studies that have already observed changes in the functionality of knee joints by measuring the range of moti- on [ 19 ]. This study reports an improvement in all of the variables monitored in those subjects who were consuming eggshell membrane, most likely resulting from physiological changes in the musculature associated with the amelioration of knee functionality and a better quality of life due to a reduction in perceived pain.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Similar conclusions have been presented in another double-blinded placebo-controlled ESM intervention trial. A total of 150 OA patients, between 45 and 70 years old, were randomly assigned to an intervention ( n = 75) or placebo ( n = 75) group [ 71 ]. After consuming 300 mg ESM powder on a daily basis for 12 weeks, patients self-reported that the treatment was successful in relieving the pain from their OA knee and contributed to improved daily life activities [ 71 ].…”
Section: Application Of Eggshell Membrane As a Novel Biomaterialsmentioning
confidence: 99%